2021
DOI: 10.1108/ijm-04-2021-0255
|View full text |Cite
|
Sign up to set email alerts
|

4.0 digital transition and human capital: evidence from the Italian Fintech market

Abstract: PurposeIn the intellectual capital literature, no studies have examined the causal relationship between Italian Fintech companies' performance and intellectual capital, especially the impact of digital industrialization on human capital. This paper aims to fill this gap in measuring human capital efficiency in the Italian Fintech market.Design/methodology/approachThe authors adopt Pulic's model and define the intellectual capital through three components (human capital, structural capital and capital employed)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
0
13
0
2
Order By: Relevance
“…Subsequently, SI's significant and positive impact on the competitive advantage has been developed sustainably. As per Izzo et al (2021), the results related to models (styles) describe regression that working capital and HC are very positive in the performance of companies. Other than that, Li et al (2020) stated the empirical results indicate that the company's positive contribution comes from the strength and efficiency of HC in different sectors.…”
Section: The Impact Of Intellectual Human Capital On Corporate Social...mentioning
confidence: 96%
See 2 more Smart Citations
“…Subsequently, SI's significant and positive impact on the competitive advantage has been developed sustainably. As per Izzo et al (2021), the results related to models (styles) describe regression that working capital and HC are very positive in the performance of companies. Other than that, Li et al (2020) stated the empirical results indicate that the company's positive contribution comes from the strength and efficiency of HC in different sectors.…”
Section: The Impact Of Intellectual Human Capital On Corporate Social...mentioning
confidence: 96%
“…Likewise, Dahiyat et al (2021) found a positive impact of HC, Social Capital, and knowledge transfer on OC. As per Izzo et al (2021), the results related to models (styles) describe regression that WC and HC are very positive in the performance of companies. Besides, Ren and Song (2021) stated HC and OC have a significant positive impact on investment in research and improvement as well as the relationship between IC and innovation, which is influenced by the drivers of the economy in general.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Berwirausaha juga memerlukan seperangkat pengetahuan dan keterampilan yang khas, cocok dengan profil tugas kewirausahaannya (Lazear, 2005;Krieger et al, 2022). Hasil penelitian Izzo et al, (2022), temuannya menunjukkan bahwa komponen modal manusia dan modal intelektual memainkan peran strategis bagi perusahaan padat pengetahuan yang tertarik untuk mempotensiasi kinerja dan daya saing mereka.…”
Section: Pendahuluanunclassified
“…A su vez, contribuye con el desarrollo nacional y regional, a través de la consolidación de trabajo colaborativo entre la universidad, empresa y estado (Guerrero et al, 2021). Además, contribuye con la atracción de talento destacado, empleabilidad y acceso a nuevas fuentes de financiamiento (Izzo et al, 2021).…”
Section: Capital Intelectualunclassified